Solution of common antenna of 4G/5G in 5G Era - Yongchang YU; Dian ZHANG; Mingling DING (Dianxin kexue)
During the 4G construction period, there were problems such as lack of antenna coverage resources at the base station site, and difficulty in coordination with residential property management.In 5G era, it is difficult to add poles at existing sites.Therefore, it is urgent to propose a solution of common antenna of 4G/5G, and to deploy quickly.The solution of 4G/5G common antenna was discussed, and a suitable solution for China Telecom’s single pole network construction was proposed.It can reduce the cost of the tower renting and network operation.At the same time, it can prove the convenience and efficiency of 5G network deployment.